Factors influencing the adoption of agricultural and forestry systems on subsistence farms: a case study in Costa Rica - Romero-Mora, María Monserrat (2023)
[Introduction]: Sustainable timber cultivation is losing ground to agricultural production and other land uses; To counteract this, it is necessary to understand how the farmer makes decisions. Therefore, management schemes must be designed that adjust to the way in which small farmers manage productive systems on a voluntary basis. [Objective]: Identify the factors that influence the decision-making process of small farmers that must be considered for the promotion of timber cultivation. [Methodology]: Surveys with open questions and single selection were applied to 100% of the farmers (N = 77) of two INDER settlements. Due to the complexity of the interactions between factors, the analysis was simplified into four approaches. The data trend was plotted from a local regression model (LOESS), in which the regression curve is generated and smoothed with the use of the geom_smooth function of the R statistical language. [Results]: A total of 162 interactions between Indirect and Direct factors. They were classified into three groups according to the number of times the farmer changed the production system in short periods (5 years). Group A has a greater representation in the population with 67.5 %, followed by Group B with 24.7 % and Group C with 7.8 %. 67.5 % of the farmers did not agree to include the cultivation of wood. [Conclusions]: It was possible to demonstrate the existence of decision factors that influence the way in which the farmers adopt the agricultural systems contrary to the cultivation of wood. Safe selling (VS) is one of them; therefore, until current forest management schemes are adjusted, the possibility of spontaneous adoption is minimal and will continue to require financial aid.